Flexor hallux tendon transfer: comparative study through double or single approach - Sakaki,Marcos Hideyo (2014)
OBJECTIVE: To quantify the FHL length difference obtained through a single approach and by a double combined approach. METHODS: 16 fresh cadavers, a total of 32 feet, were used to measure the FHL graft length. With the cadaver positioned in ventral decubitus, a posteromedial incision in the ankle and a second incision in the plantar cavus were performed. RESULTS: The average gain of tendon's length (GTL) was of 42.43 mm, the lowest value being 32 mm and the largest 48 mm. The comparative analysis of the GTL on the right and left sides through the paired "t" Test does not show statistical differences, with a p-value = 0.463 and a statistical power of 0.1443. The height analysis of the sample and the right and left GTL performed through linear regression do not show statistically significant differences, with a p-value of 0.38311 and 0.82640, respectively. CONCLUSION: Harvesting the FHL graft using a double combined approach yields a 42.43 mm length gain in comparison to harvesting using the single approach. Level of Evidence III, Case Control Study.